Ultimate Salesforce LWC Developers' Handbook - Hizar, Cihan Fethi (Orange Education PVT Ltd, 2023)
Embark on a transformative journey into the world of Salesforce Lightning Web Components (LWC) with this comprehensive guide. From laying the foundation to honing advanced skills in LWC debugging and testing, each chapter seamlessly builds upon the last, empowering developers to navigate the intricate world of Salesforce LWC development. The book begins by creating your first LWC and delving into the intricacies of Lightning Web Components. It explores the seamless integration of Salesforce Data and master event management with Events in LWC. Next, it moves on to navigate the relationship between LWC and Flows, unlocking the potential of Lightning Out for standalone applications. Readers will dive deep into the aesthetics with Salesforce Lightning Design System, enhancing their components with style. It will also help you safeguard your applications by understanding LWC Security measures and learn debugging and testing in the LWC environment. In the final chapters, immerse yourself in working with Aura components and seamlessly migrate them to LWCs, providing an insightful transition to advanced development techniques.